2004
DOI: 10.1523/jneurosci.0765-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ/M Channels Control Spike Afterdepolarization and Burst Generation in Hippocampal Neurons

Abstract: KCNQ channel subunits are widely expressed in peripheral and central neurons, where they give rise to a muscarinic-sensitive, subthreshold, and noninactivating K ϩ current (M-current). It is generally agreed that activation of KCNQ/M channels contributes to spike frequency adaptation during sustained depolarizations but is too slow to influence the repolarization of solitary spikes. This concept, however, is based mainly on experiments with muscarinic agonists, the multiple effects on membrane conductances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
362
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 331 publications
(399 citation statements)
references
References 54 publications
(70 reference statements)
25
362
0
2
Order By: Relevance
“…Yue et al found that bursting behavior persists in adult CA1 pyramidal cells after almost complete truncation of the apical dendrites. The bursting mechanism is different from the 'ping-pong' mechanism, which depends on integrity of apical dendrites [25][26][27]. Based on the CA1 pyramidal neuron's membrane ionic channel theory and its electrophysiological experimental data, according to the basic frames of the Hodgkin-Huxley(H-H) class of neuron models, Golomb et al developed the one-compartment model of CA1 pyramidal neuron [5], which is different from the former multi-compartment cable model of the hippocampal pyramid neuron.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Yue et al found that bursting behavior persists in adult CA1 pyramidal cells after almost complete truncation of the apical dendrites. The bursting mechanism is different from the 'ping-pong' mechanism, which depends on integrity of apical dendrites [25][26][27]. Based on the CA1 pyramidal neuron's membrane ionic channel theory and its electrophysiological experimental data, according to the basic frames of the Hodgkin-Huxley(H-H) class of neuron models, Golomb et al developed the one-compartment model of CA1 pyramidal neuron [5], which is different from the former multi-compartment cable model of the hippocampal pyramid neuron.…”
Section: Introductionmentioning
confidence: 91%
“…They have studied electrophysiological characteristics of the neuron under the morbid state of AD, and have acquired many research findings and conclusions [15,18,20,22]. Xiaoliang Wang [15] simulated the morbid state of AD by injecting the aggregated Aβ [25][26][27][28][29][30][31][32][33][34][35] into the lateral ventricle. They recorded and studied the electrophysiological characteristics' change of the hippocampal pyramid neuron's voltage-gated currents (the A-type instantaneous K + current (I A ) and the delay rectification K + current (I Kdr )) under the morbid state of AD.…”
Section: The Hippocampal Neuron's Electrophysiological Characteristicmentioning
confidence: 99%
See 3 more Smart Citations